(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
The scientific article is devoted to the issue of interdependence in the energy sector between different regions of the world in the example of EU-EAEU cooperation. The purpose of this study is to analyze the role of the energy factor as a connecting and integrating element of regional economic interaction between the EU and the EAEU. Using the theoretical paradigms of realism, liberalism, constructivism, the article analyzes the relationship between the EU and the EAEU in the context of ensuring future stability in the energy sector in Europe related to the ability of the countries of the European Union (EU) and the EAEU to support the interdependence of the energy market. While writing the article, the author studied and summarized the studies of scholars of the realism paradigm, whose writings discussed the influence of economic interdependence on states’ intentions to initiate conflicts, as well as neoliberal school followers like R. Keohane and J. Nye who conceptualize interdependence and define it as the existence of interdependence between international actors in various fields of their interaction. Based on the data obtained, it was found that an analysis of energy relations between the EU and the EAEU in recent years confirms the hypothesis that the political consequences of interdependence are not a simple function of growing trade and investment relations. By analyzing the political impact of energy interdependence, one can focus not only on existing or planned pipelines, the development of market conditions, the structure of energy prices, the dynamics of exports and imports, and the extent of interdependence. Key words: EU, EAEU, interdependence, energy interests, cooperation, international relations